Reforming the Humanities - Levine, P. author. aut Link
VII, 236 p.
Keywords: Through an analysis of Dante's story of Paolo and Francesco, this book combines contemporary ethical theory, literary interpretation, and historical narrative to defend the humanities as a source of moral guidance.